PRIORITAS PENGGUNAAN DANA DESA DALAM BIDANGPEMBERDAYAAN MASYARAKAT DI DESA TANJUNG ALAI KECAMATAN XIII KOTO KAMPARKABUPATEN KAMPAR TAHUN 2016-2017 - ", Bendrianto; Febrina, Rury (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The priority setting for using village funds for community empowerment according to ministerial regulation number 21 of 2015 is not in accordance with applicable regulations. The Village Fund is prioritized to finance development expenditure and empower village communities. But in reality, in Tanjung Alai Subdistrict XIII Koto Kampar, Kampar Regency still has not allocated village funds for the Community Empowerment program in 2016-2017 in accordance with applicable regulations.There are many factors that influence in the decision making process, the formulation of village policies through the Village Regulation to determine the APBDes which contains the priority of village funds for village development programs, including: 1) Factors of domination of village elites, 2) Factors of limited funds for village development funds 3) Factors the lack of participation of village communities 4) the weak factor of village institutions. Suggestions in this research include, need to be explored and developed Village Original Revenue (PAD) especially the potential natural resources and human resources of Tanjung Alai Village community in order to obtain other sources of income for empowerment programs, increase community participation in Musrenbangdes activities and the strengthening of the Village Consultative Body (BPD) in order to pay more attention to the aspirations of the community while controlling the implementation of village development in accordance with applicable regulations.Â Keywords: Village Funds, Community Empowerment Priorities